VD_FINDINFO AP / 2011 / 69 vom 13. April 2011 - VD Tribunal cantonal (2011)
EXCEPTIONMOYEN DE DÉFENSE, DÉCISION D'IRRECEVABILITÉ, ACTION EN CONSTATATION | 138 CPC, 142 CPC, 285 CPC, 451 ch. 3 CPC, 456a CPC